Universal mathematical model of three-phase electrical transmission lines; 11th International Forum on Strategic Technology (IFOST 2016); Pt. 2 - Andreev M. V. Mikhail Vladimirovich (Power engineering and renewable energy technologies, 2016)
Title screen